EN LA CIUDAD DE SYLVIA O LA CIUDAD DEL FLÂNEUR - Dda. Luz Marina ORTIZ AVILÉS (Fonseca, Journal of Communication, 2023)
The flâneur, a figure mainly related to artistic disciplines such as literature, painting and photography, has been scarcely approached in cinema. Although it is possible to find some films where this figure has been slightly insinuated, up to now we had not been able to find a cinematographic work that we can take as an obvious reference. We think José Luis Guerin’s En la ciudad de Sylvia manages to fill that referential gap. Therefore our analysis and reflections try to shed light on the relations between the main character of the film and the flâneur.